2017
DOI: 10.1007/s11274-017-2337-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antitumor activity of Bogorol B-JX isolated from Brevibacillus laterosporus JX-5

Abstract: Antimicrobial peptides are promising anti-infective agent candidates because they have a broad antimicrobial spectrum and bioactivity and are unlikely to elicit antibiotic resistance. The bogorols represent a new cationic antibiotic peptide and possess great therapeutic potential because of their bioactivity and precise mode of action. Here, we report that Bogorol B-JX (BBJX), a peptide previously isolated from Brevibacillus laterosporus JX-5 by us, has significant antibacterial and antitumor activities in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…And our finding indicated that Brevilaterin C could obviously induce apoptosis and increase ROS levels of A431 cells, in a similar manner to that reported for other pentapeptides against the HL‐60 cell line 35 . Compared with 3 µg/ml of Brevilaterin C, another bacterial AMPs Bogorol B‐JX at 10 µg/ml isolated from the same bacterium B. laterosporus JX‐5 could display a similar effect on ROS generation in U‐937 cells 21 . The mitochondrial electron transport chain is the major source of ROS; moreover, when the function or integrity of the chain is compromised, (e.g., by treatment with uncoupling agents), excessive amounts of ROS are generated 21 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…And our finding indicated that Brevilaterin C could obviously induce apoptosis and increase ROS levels of A431 cells, in a similar manner to that reported for other pentapeptides against the HL‐60 cell line 35 . Compared with 3 µg/ml of Brevilaterin C, another bacterial AMPs Bogorol B‐JX at 10 µg/ml isolated from the same bacterium B. laterosporus JX‐5 could display a similar effect on ROS generation in U‐937 cells 21 . The mitochondrial electron transport chain is the major source of ROS; moreover, when the function or integrity of the chain is compromised, (e.g., by treatment with uncoupling agents), excessive amounts of ROS are generated 21 .…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, only one report published by Jiang described the bioactivity of AMPs from B. laterosporus toward human cancer cells. They indicated that Bogorol B‐JX efficiently inhibition proliferation of the human histiocytic lymphoma cell line U‐937 21 . However, there had never addressed a systematic exploration of the anticancer properties of AMPs from B. laterosporus toward different human tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brevibacillus laterosporus , one of the most valuable biocontrol bacterias for its insecticidal activity, 23 has attracted more and more attention recently because of its antibacterial activity 24–27 . Wang et al characterized a novel protein elicitor PeBL1 from B. laterosporus strain A60.…”
Section: Introductionmentioning
confidence: 99%
“…The medical interest is related to the synthesis of antibiotics acting against diverse human pathogenic fungi and bacteria, including Candida albicans [2], Escherichia coli, Klebsiella, Pseudomonas, Salmonella, Staphylococcus, and Streptococcus species [3,4]. Antitumor compounds from B. laterosporus have also found specific medical applications [5,6]. In the field of agriculture, the high biocontrol potential of this bacterial species relies on the production of a variety of toxins, enzymes, and other virulence factors acting against phytopathogens and invertebrate pests, including insects, nematodes, and molluscs [1].…”
mentioning
confidence: 99%